Developing Chemistry Lesson Plan Design: Integrating Scientific Explanation by CER Framework in STEM Learning - Laksono, Pandu Jati; Ari S Shidiq; Irfan Yunianto; Evelina A Patriot (Chemistry Education Department of Education and Teaching Faculty, 2024)
The main supporting component of a comprehensive learning implementation, scientifically prepared according to the chemical context, is developing a chemistry lesson plan. Scientific explanations in chemistry learning often involve causal mechanistic explanations of chemical phenomena, which provide a paradigm for understanding chemical concepts. This research aims to describe how prospective chemistry teachers use scientific explanations to develop CER framework in chemistry lesson plans that align with STEM learning. A descriptive qualitative research design was used. The authors conducted this research on 20 prospective chemistry teachers. This research used the document review, observation, CER framework assessment, and interviews. Prospective chemistry teachers can theoretically and practically prepare chemistry learning plans. The study reveals that prospective chemistry teachers struggle to offer scientific explanations for the concepts they explain through CER framework. Their responses to the CER framework assessment reveal numerous unconnected scientific explanations. One cannot combine evidence and reasoning claims into a systematic unity to explain a chemical phenomenon.